SURVEY OF INTRADIALYTIC HYPOTENSION IN THE END-STAGE RENAL DISEASE PATIENTS ON THEIR FIRST HEMODIALYSIS SESSION - Nguyen Dinh Kinh; Quach Anh Tuan; Le Dang Phu; Nguyen Thi Hien; Le Ngoc Thanh (Tạp chí Y học Quân sự, 2026)
Objective: To determine the rate of intradialytic hypotension and identify several related factors in patients with end-stage renal disease undergoing their first hemodialysis session. Methods: A descriptive cross-sectional study was conducted on 54 patients diagnosed with end-stage renal disease who underwent their first hemodialysis session at the Hemodialysis Center, Thanh Hoa General Hospital, from January 2025 to October 2025. Results: The prevalence of intradialytic hypotension among first-time hemodialysis patients with end-stage renal disease was 14.8%, of which 75% of hypotensive episodes occurred during the second half of the dialysis session. Patients aged > 60years, blood glucose ≥ 10 mmol/l, serum albumin ≤ 30 g/l, and ultrafiltration rate > 750 ml/h had a significantly higher risk of developing intradialytic hypotension compared with the remaining groups (p < 0.05). Conclusion: The prevalence of intradialytic hypotension in first-time hemodialysis patients with end-stage renal disease was relatively high (14.8%), occurring predominantly during the latter half of the dialysis session. Advanced age (> 60 years), hyperglycemia (≥ 10 mmol/l), hypoalbuminemia (≤ 30 g/l), and high ultrafiltration rate (> 750 ml/h) were significant risk factors associated with intradialytic hypotension.